Foaming behavior of bio‐based blends based on thermoplastic gelatin and poly(butylene succinate). Issue 48 (24th July 2015) - Oliviero, Maria; Sorrentino, Luigi; Cafiero, Livia; Galzerano, Barbara; Sorrentino, Andrea; Iannace, Salvatore; Pantani, Prof. Roberto; Turng, Prof. Lih‐Sheng
ABSTRACT Biodegradable thermoplastic gelatin/poly(butylene succinate) (TPG/PBS) foams were prepared by melt mixing and subsequent batch foaming with supercritical CO2. Shear viscosity and calorimetric properties of the various blends were investigated using a rotational rheometer and a differential scanning calorimeter, respectively. TPG/PBS blends show poor miscibility at all blend ratios. The addition of PBS reduced the melt viscosity and increased both the CO2 diffusivity and the thermal stability of TPG. Results from foaming experiments show that the blend foams exhibit smaller cell size and higher cell density compared to the neat TPG foam due to the lower melt viscosity and to their lower gas barrier. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42704.